Cold Compression and Kinesio Taping to Accelerate Football Athletes' Injury Recovery - Hamzah, Alimin; Berliana, Berliana; Pitriani, Pipit; Hasmyati, Hasmyati (JUMORA: Jurnal Moderasi Olahraga, 2024)
The likelihood of injury because of sports is normal, particularly in soccer sports that have the potential for body contact. One of the ongoing injury treatment is using Cold Compression and Kinesio Taping. The aim of this study was to decide the impact of the utilization of Cold Compression combined with Kinesio Taping on Achilles Ligament wounds and Patella wounds of football competitors. The research method used in this study is a quasi-experiment with the research design of The Non-Equivalent Control Group Design. In this study we use instruments VISA-A (Victorian Establishment of Game Evaluation Achilles), VISA-P (Patella) and ROM (Range of Motion) to quantify the degree of agony experienced by partisipants. Partisipants in this study were football athlete who suffered an injury adding up to 19 partisipants, going in age from 16 to 24 years. We used a purposive sampling approach used with several participant criteria and incidental sampling. There are two groups, namely the group given treatment in the form of Cold Compression combined with Kinesio Taping, there are 9 athletes in this group with details of 5 Achilles injured athletes and 4 Patella injured athletes. The second group was a control group of 10 athletes with details of 5 Achilles injured athletes and 5 Patella injured athletes. The study was conducted for 8 days with the distribution of 4 days Cold Compression treatment and 4 days Kinesio Taping treatment. The analysis requirements tests used are normality tests, homogeneity tests, and for hypothesis tests using paired sample t-tests (parametrics). The results showed a significant effect on the Cold Compression group combined with Kinesio Taping compared to the control group. For future researchers, it is recommended to examine using different methodologies and with different types of injuries.